2021
DOI: 10.1002/lt.26067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ex Situ Hypothermic Oxygenated Machine Perfusion and Cold Preservation Time in Extended Criteria Donation After Circulatory Death and Donation After Brain Death

Abstract: Hypothermic oxygenated machine perfusion (HOPE) has the potential to counterbalance the detrimental consequences of cold and warm ischemia time (WIT) in both donation after brain death (DBD) and donation after circulatory death (DCD). Herein we investigated the protective effects of HOPE in extended criteria donor (ECD) DBD and overextended WIT DCD grafts.The present retrospective case series included 50 livers subjected to end-ischemic HOPE or dual DHOPE in 2 liver transplantation (LT) centers from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Previous retrospective studies in the setting of DBD LT 9,11 have suggested that D-HOPE reduces ischemia-reperfusion injury and translates into better postoperative outcomes. In our previous study, 12 D-HOPE use was associated with a reduced rate of postreperfusion syndrome, grade 2-3 AKI and early allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies in the setting of DBD LT 9,11 have suggested that D-HOPE reduces ischemia-reperfusion injury and translates into better postoperative outcomes. In our previous study, 12 D-HOPE use was associated with a reduced rate of postreperfusion syndrome, grade 2-3 AKI and early allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that end‐ischemic D‐HOPE of livers from DBD donors is associated with a significant reduction of postoperative complications and EAF, leading to improved patient and graft survival. Previous retrospective studies in the setting of DBD LT 9,11 have suggested that D‐HOPE reduces ischemia‐reperfusion injury and translates into better postoperative outcomes. In our previous study, 12 D‐HOPE use was associated with a reduced rate of postreperfusion syndrome, grade 2–3 AKI and early allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when the donor liver is reallocated to another recipient in the last minute, or in the event of a difficult recipient hepatectomy. [7][8][9] Good outcomes after prolonged normothermic machine perfusion (NMP) up to 20 h have been reported previously, 10 but the use of prolonged HOPE is still unexplored. In a preclinical study of porcine and discarded human livers, HOPE could succesfully be prolonged for up to 24 h, followed by normothermic reperfusion.…”
Section: Introductionmentioning
confidence: 93%
“…Whereas a brief period (usually 1–2 h) of HOPE after SCS improves post‐transplant outcomes, machine perfusion time may occasionally be prolonged because of unforeseen transplant logistics. For example, when the donor liver is reallocated to another recipient in the last minute, or in the event of a difficult recipient hepatectomy 7‐9 . Good outcomes after prolonged normothermic machine perfusion (NMP) up to 20 h have been reported previously, 10 but the use of prolonged HOPE is still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen (47%) grafts were subjected to MP, where 10 were procured from DCD and 8 from DBD-ECD donors meeting the criteria specified above, except for livers 18 and 19, which were subjected to MP to extend the preservation time because of logistic reasons (change of recipient) [36,45,52].…”
Section: Donor Characteristics and Liver Graft Allocation To The Mp Proceduresmentioning
confidence: 99%